Policy-Related Determinants of Child Nutritional Status in China : The Effect of Only-Child Status and Access to Healthcare - Bredenkamp, C. (2012)
This paper examines the determinants of child nutritional status in China, focusing specifically on those determinants related to health system reform and only-child status. Data are drawn from four waves of the China Health and Nutrition Survey (1991-2000). The empirical relationship between nutritional status, on the one hand, and income, access to quality healthcare and being an only-child, on the other hand, is investigated using ordinary least squares (OLS), random effects (RE), fixed effects (FE) and instrumental variables (IV) models. In the preferred model - a fixed effects model where income is instrumented - we find that being an only-child increases height-for-age z-scores by 0.12 of a standard deviation. By contrast, measures of access to quality healthcare are not found to be significantly associated with improved nutritional status.